2022
DOI: 10.1186/s13049-021-00985-0
|View full text |Cite
|
Sign up to set email alerts
|

Remote real-time supervision of prehospital point-of-care ultrasound: a feasibility study

Abstract: Background Although prehospital point-of-care ultrasound (POCUS) is gaining in importance, its rapid interpretation remains challenging in prehospital emergency situations. The technical development of remote real-time supervision potentially offers the possibility to support emergency medicine providers during prehospital emergency ultrasound. The aim of this study was to assess the feasibility of live data transmission and supervision of prehospital POCUS in an urban environment and so to imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Additionally, the actual use of POCUS by trained providers has been shown to increase as time spent training increases, underscoring the importance of supervised scanning to allow practitioners to become comfortable using this tool (Leschyna et al, 2019). Concerns regarding the accuracy of POCUS interpretation by prehospital providers could be mitigated by real-time interpretation of prehospital practitioner-generated images by a radiologist or other trained provider (Hermann et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the actual use of POCUS by trained providers has been shown to increase as time spent training increases, underscoring the importance of supervised scanning to allow practitioners to become comfortable using this tool (Leschyna et al, 2019). Concerns regarding the accuracy of POCUS interpretation by prehospital providers could be mitigated by real-time interpretation of prehospital practitioner-generated images by a radiologist or other trained provider (Hermann et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the hospital, point-of-care ultrasound (POCUS) has become an increasingly popular bedside tool for the assessment of similarly undifferentiated patients by emergency physicians, allowing for early and accurate diagnosis of life-threatening diagnoses such as ectopic pregnancy, abdominal aortic aneurysm, and cardiogenic shock (Lewis et al, 2019). Recent technological advances have allowed for the expansion of handheld POCUS to the prehospital environment, offering an innovative way for prehospital practitioners to improve their diagnostic accuracy (Hermann et al, 2022;Smallwood & Dachsel, 2018). Moreover, several studies have identified the feasibility of POCUS by non-physicians (Amaral et al, 2020;Becker et al, 2018;Bøtker et al, 2018;Laursen et al, 2016;Nadim et al, 2021;Pietersen et al, 2021), with non-physician practitioners identifying conditions such as cardiogenic pulmonary edema and abdominal aortic aneurysm with high sensitivity and specificity (Laursen et al, 2016;Schoeneck et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Rather than focusing on supporting individuals who are practicing on their own, services could be reconfigured in a way that would facilitate closer teamwork. With the assistance of modern communication technology, it would be relatively easy to organize services such that expert examiners could support directly, or remotely, a relatively large number of sonographers in real time 16 . This support could include assistance with technical aspects of the examination, help with diagnosis and advice on management and follow‐up.…”
mentioning
confidence: 99%
“…Modernisation of communication technologies allowed to deliver POCUS to the prehospital setting using remote real-time supervision by a trained specialist. 6 The COVID-19 pandemic further exposed limitations of traditional clinical chest auscultation 7 and non-bedside diagnostics that required in-hospital and interhospital patient transport. This led to an 'explosion' of POCUS during the surge crisis.…”
mentioning
confidence: 99%
“…The expansion can be in part explained by the significant miniaturisation and reduced costs of ultrasound scanners, incorporation of artificial intelligence and gradually increased number of trainers in all medical specialties. Modernisation of communication technologies allowed to deliver POCUS to the pre‐hospital setting using remote real‐time supervision by a trained specialist 6 . The COVID‐19 pandemic further exposed limitations of traditional clinical chest auscultation 7 and non‐bedside diagnostics that required in‐hospital and interhospital patient transport.…”
mentioning
confidence: 99%